Peripheral blood T-cell subsets combined with EGRIS score predict the need for mechanical ventilation in Guillain–Barré syndrome - Jia, Feihong; Wang, Xinrui; Chen, Yuan; Li, Yunshu; Du, Xinshu; Chen, Hongping; Zhong, Di (Frontiers in Immunology, 2026)
BackgroundThe pathogenesis of Guillain–Barré syndrome (GBS) may involve lymphocyte-mediated immune mechanisms. This study aimed to investigate the relationship between peripheral blood lymphocyte subsets and disease onset, severity, and the need for mechanical ventilation in patients with GBS.MethodsThis cohort study included 55 patients with GBS and 58 healthy controls. The association between peripheral blood lymphocyte subsets and the onset and severity of GBS was investigated. Among the GBS patients, 26 were classified into a non-mechanical ventilation group and 29 into a mechanical ventilation group, and the predictive value of peripheral blood lymphocyte subsets for mechanical ventilation was evaluated. Furthermore, the study examined the expression of relevant lymphocyte subsets in the sciatic nerve of experimental autoimmune neuritis (EAN) rat models at different disease stages.ResultsROC curve analysis showed that both CD8+ T cell counts and NK cell counts had moderate discriminative ability in distinguishing patients with GBS from controls. The AUC for CD8+ T cell counts was 0.73 (95% CI: 0.637–0.836), with an optimal cutoff value of 394.39 cells/μL, while the AUC for NK cell counts was 0.81 (95% CI: 0.731–0.893), with an optimal cutoff value of 147.7 cells/μL. Total lymphocyte counts, total T cell counts, CD8+ T cell counts, and CD4+ T cell counts were negatively correlated with Hughes peak score (all P ≤ 0.005). Logistic regression showed that higher peripheral CD4+ T cell counts was associated with reduced need for mechanical ventilation (OR = 0.997; 95% CI: 0.994–1.000, P = 0.032). The combined ROC analysis of CD8+ T cell counts, CD4+ T cell counts, and the EGRIS score demonstrated good discriminative ability for identifying GBS patients who required mechanical ventilation, with an AUC of 0.87 (95% CI, 0.772–0.971, P < 0.001). In the EAN model, CD4+ T cell expression was increased in sciatic nerve tissue.ConclusionPeripheral blood lymphocyte subsets show potential value in differentiating disease severity and the need for mechanical ventilation in patients with GBS, highlighting the clinical significance of immune cell profiling in risk stratification.